Understanding barriers to access and utilization of cervical cancer screening services among women living with HIV in Kenya and Uganda - Wycliff, Katwesige; Cordova-Pozo, Kathya; Hagono, Peter; Daniel, Ebenezer, Obi; Kalam, Abul (My University, 2021)
Background: Invasive cervical cancer (ICC) is one of the most preventable and curable forms of cancer. In East Africa, primarily Uganda and Kenya, where HIV/AIDs are common, it is usually diagnosed late, resulting in a public health hazard due to its poor prognosis. ICC is the second most common malignancy causing maternal death. This study explored factors that impede access and utilization of ICC screening services among women living with HIV in low resource settings in Uganda and Kenya. Methods: A cross-sectional study design employing qualitative and quantitative techniques were conducted in six selected health facilities in Uganda and Kenya. A systematic cluster randomized sampling was used to select health facilities from which women living with HIV were invited to participate in the interviews, including focus group discussions, and triangulated this with in-depth interviews and literature. Data collection, coding, categorization, and statistical analysis of quantitative data were employed to rank correlation among the most critical factors that hinder access to ICC screening services. Findings: Two hundred thirty-two (232) out of 310 women completed the interviewer-administered questionnaire making the response rate 75%. The results uncovered a negative correlation between the perception of barriers to access the services. Two variables, the perceived risk for having ICC and the perceived severity, may impact the likelihood of undergoing ICC screening. There was a positive correlation between the perceived risk for ICC and the perceived severity. Statistical analysis shows that results are valid and reliable. Conclusion: The study uncovered the health system barriers affecting ICC screening services at health facilities in Kenya and Uganda. It highlights the strengths and challenges while providing recommendations to promote health to include the most vulnerable women with HIV/AIDS living in socially deprived areas.
Supplemental Materials: https://osf.io/kr362/
Keywords: Cervical cancer screening; Health Belief Model; Low-resource setting; Uganda and Kenya; women with HIV/AIDs